Sunburn in children and adolescents: associations with parents' behaviour and attitudes. Issue 3 (May 2013) - Behrens, Christine L.; Thorgaard, Camilla; Philip, Anja; Bentzen, Joan
Aims : Sunburn in childhood is a known risk factor for melanoma and non-melanoma skin cancer. Based on a theoretical model, we tested the hypothesis that parental attitudes and behaviour are related to the risk of sunburn in their children. Methods : We analysed the association between behaviour in the sun and attitudes related to tanning among Danish parents and their children's risk for sunburn by logistic regression. Gender, educational level, and skin type of the responding parent were included as confounders and analyses were stratified for child age. Results : In children aged 7–12 and 13–17 years, the risk of sunburn increased when parents had experienced sunburn themselves, and also for 13–17 year olds if parents had a very positive attitude towards tanned skin. We found no association between parental attitudes and behaviour and the risk of sunburn in children aged 0–6 years. Conclusions : Interventions to influence the attitudes and behaviour of parents could reduce their children's risk for excessive sun exposure and thereby their risk for melanoma and non-melanoma skin cancer. The results encourage preventive campaigns to focus on changing parental attitudes towards tanned skin and sun behaviour .